Bread, bread, bread - Morris, Ann, 1930-; Heyman, Ken (New York : Mulberry Books, 1993)
Celebrates the many different kinds of bread and how it may be enjoyed all over the world.
Includes index.
Wilson's Children, October 2010.
Elem. School Library Collection, March 1998.
School Library Journal starred, May 1989.
School Library Journal, January 1996.
Book Links (A.L.A.), February 2002.
Keywords: Bread -- Juvenile literature; Bread